2022
DOI: 10.31234/osf.io/zqc2x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial Thinking in Practice: A snapshot of teacher’s spatial activity use in the early years’ classroom.

Abstract: Spatial thinking predicts Science, Technology, Engineering and Mathematics achievement, yet is often absent from educational policy. We provide the first benchmarks of teachers’ usage and perceptions of spatial activities in practice in the reception classroom. Using a questionnaire study with educational professionals working in the reception (4-5 years) classroom in England (N=104), we found that spatial and numeracy activities were perceived as significantly less important, and were completed significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The included apps primarily targeted basic skills in understanding number representations and relationships ( n = 21) with number representation with Arabic digits, verbal and/or written number word recognition as the most common ( n = 19) (see Table S2). This is also consistent with previous research showing a greater emphasis on basic counting skills in the classroom (von Spreckelsen et al, 2019) and a relatively reduced focus on spatial skills in formal classroom activities (Gilligan‐Lee et al, 2022). However, mathematical development is complex and consists of a broad range of skills that children need to master (Butterworth, 2005; Clements & Sarama, 2009; Gilmore et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…The included apps primarily targeted basic skills in understanding number representations and relationships ( n = 21) with number representation with Arabic digits, verbal and/or written number word recognition as the most common ( n = 19) (see Table S2). This is also consistent with previous research showing a greater emphasis on basic counting skills in the classroom (von Spreckelsen et al, 2019) and a relatively reduced focus on spatial skills in formal classroom activities (Gilligan‐Lee et al, 2022). However, mathematical development is complex and consists of a broad range of skills that children need to master (Butterworth, 2005; Clements & Sarama, 2009; Gilmore et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Whilst SR does now feature in the statutory educational programme for birth to fiveyear-olds in England, 'shape, space and measures' was removed from the statutory early learning goals in mathematics for the end of this phase of a child's education (DfE, 2021), something which is likely to 'reduce the emphasis' in practice, according to a finding from the pilot study of the new goals (Husain et al, 2019, p.22). It is therefore unsurprising that in another study (N=104), we found that practitioners working with 4-5-year-olds perceive spatial and numeracy activities as less important than literacy and life skills and completed these activities less frequently (Gilligan-Lee et al, 2023)…”
Section: The Research-practice Divide In Sr Practice With Young Childrenmentioning
confidence: 75%
“…Participants were first asked how frequently they used each of 18 activities (12 spatial and 6 non‐spatial, presented in fixed random order, adapted from Gilligan‐Lee et al. ( 2022 ) in their practice using 6 possible response options, ranging from ‘More than once a day’ to ‘Not at all’ as shown in Figure 1 . This question was deliberately posed before any questions that asked about spatial reasoning, to avoid introducing bias.…”
Section: Methodsmentioning
confidence: 99%